Information Framework of Critical Infrastructure - Stanislava Mildeová (Acta Informatica Pragensia, 2016)
Information and communication technologies are in connection with security discussed by professional community from many perspectives. The authors perceive information and communication technologies as potential as well as threat to the security environment. The aim of the article is to holistically analyze the basic connection between the information framework and functionality of the critical infrastructure system involved in the activities of the public administration. As a model case is discussed the protection of critical infrastructure against toxic substances. Turbulence of the security environment, conflict transformation into hybrid or asymmetric forms and, as it is proven in the article, a crucial position of informatics in these processes makes this a very actual topic.